Literatur Rivew Pengaruh Konseling Gizi Terhadap Kepatuhan Diet Pasien Diabetes Mellitus Tipe-2 - Sakhwa Agustin; Ratih Kurniasari (Jurnal Gizi dan Kuliner, 2023)
The 2017 International Diabetes Federation shows that as many as 10.3 million people in Indonesia suffer from diabetes and are ranked 6th in the world with the largest number of diabetics (RI Ministry of Health, 2018). Based on the 2018 Riskesdas, the prevalence of diabetes increased to 8.5% from 6.9%. Diabetes mellitus is a metabolic degenerative disease caused by the pancreas being unable to produce enough insulin. The most common type of diabetes mellitus is type-2 diabetes mellitus. The provision of nutritional counseling is very important because it is a disease related to lifestyle. The purpose of nutritional counseling is to change attitudes and behavior so that they are in accordance with the goals of diet management. Patient compliance with what is given during counseling will affect success in undergoing diet management. This research aimed To determine the effect of nutritional counseling on dietary adherence in type-2 diabetes mellitus patients. Method: Using the literature review method by comparing several literature materials. The result showed that nutrition counseling affects dietary adherence in type-2 diabetes mellitus patients. Nutritional counseling with the principle of regulating the type of food, the number of calories and the meal schedule can affect dietary adherence in type-2 diabetes mellitus patients. Keywords: Nutrition counseling, Dietary compliance, Diabetes Mellitus